2022
DOI: 10.3390/antiox11122457
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol Release from Wheat Bran Using Ethanol-Based Organosolv Treatment and Acid/Alkaline Catalysis: Process Modeling Based on Severity and Response Surface Optimization

Abstract: Wheat bran (WB) is globally a major food industry waste, with a high prospect as a bioresource in the production of precious polyphenolic phytochemicals. In this framework, the current investigation had as objectives (i) to use ethanol organosolv treatment and study the effect of acid and alkali catalysts on releasing bound polyphenols, (ii) establish linear and quadratic models of polyphenol recovery based on severity and response surface, and (iii) examine the polyphenolic composition of the extracts generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 53 publications
2
13
1
Order By: Relevance
“…As can be seen in Figure 3 , alkaline hydrolysis resulted in an extract enriched in ferulic acid (FA), which, based on earlier studies, was the anticipated outcome [ 29 ]. However, p -coumaric acid ( p -CA), which may usually accompany FA, was not detected.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…As can be seen in Figure 3 , alkaline hydrolysis resulted in an extract enriched in ferulic acid (FA), which, based on earlier studies, was the anticipated outcome [ 29 ]. However, p -coumaric acid ( p -CA), which may usually accompany FA, was not detected.…”
Section: Resultsmentioning
confidence: 88%
“…The Y TP values attained with 10% citric acid and sodium carbonate were 23.76 and 23.60 mg FAE g −1 DM, respectively. These yields may be considered exceptionally high, in the light of recent studies that reported levels of 19.76 ± 0.76 mg FAE g −1 DM, achieved with hydroethanolic solutions and sodium hydroxide catalysis [ 29 ]. In general, it has been demonstrated that the conventional extraction of WB with commonly used solvents could afford only low Y TP levels, i.e., 0.84 mg FAE g −1 DM for aqueous ethanol extraction [ 30 ], 4.66 mg GAE g −1 DM for 50% acetone extraction [ 31 ], and 5.90 mg caffeic acid equivalents g −1 DM for deep eutectic solvent extraction [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations